ORGANIC GEOCHEMICAL AND ORGANIC PETROGRAPHIC CHARACTERIZATION OF UPPER MEMBER OF TELISA FORMATION OIL SHALES - Anggadipa Gemilang, Romanda
Administratively, research area is located in Pangkalan and surrounding areas, Kuantan Singingi Regency, Riau Province. Geologically, research area is located in Central Sumatra Basin. Shale samples amount used in this research are eleven and taken by outcrop drilling which is conducted in Upper Member of Telisa Formation. Based on drilling data, shale oil layers in research area consist of four layers, they are A Layer, B Layer, C Layer, and D Layer. Analyses of organic geochemistry and organic petrography were conducted to eleven samples of Upper Member of Telisa Formation to determine characteristic of quantity, maturity, and quality of organic matter. Analyses of organic geochemistry and organic petrography which were conducted consist of Rock-Eval pyrolysis, vitrinite reflectance analysis, and organic matter composition analysis. Based on analysis results, oil shales in A and B Layers have good to excellent quantity category, immature stage of maturity, and belong to type I and II, meanwhile oil shales in C and D Layers have poor quantity category, immature stage of maturity, and belong to type III. Based on maceral composition data, it is known that A and B Layers composition is dominated by alginite maceral, meanwhile C and D Layers compositon is dominated by vitrinite maceral. Oil shales characteristic that had been determined is compared with retort data result in research area. Comparison result shows that amount of oil from retorting has linear positive relationship with value of alginite percentage, TOC, S1, S2, S3 and HI, meanwhile amount of oil from retorting has linear negative relationship with value of mineral percentage and OI. Based on maceral composition data and core data, depositional environment of A and B Layers is interpreted in freshwater lacustrine, while depositional environment of C and D Layers is interpreted in estuary. Based on retort data and calculation of production cost, it could be concluded that oil shales in Upper Member of Telisa Formation in research area when the study is conducted is not economically produced.